Animal Cell Technology: Basic &Amp; Applied Aspects 2003
DOI: 10.1007/978-94-017-0726-8_36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvacrol on a Human Non-Small Cell Lung Cancer (NSCLC) Cell Line, A549

Abstract: Carvacrol, the predominant monoterpene in many essential oils of Labitae including Origanum, Satureja, Thymbra, Thymus, and Corydothymus has substantial antibacterial, antifungal, antihelmintic, insecticial, analgesic and antioxidant activities. Approximately 75% of lung cancer is non-small cell carcinoma (NSCLC) which comprises several histologic types squamous cell, adenocarcinoma and large cell carcinoma. It was reported that the portion of lung tumors diagnosed as denocarcinoma has increased. Thus a human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 11 publications
2
62
0
1
Order By: Relevance
“…They induced membrane and DNA damage and cytotoxicity in H1299 cells at relatively higher concentrations than those that mediate their anticancer activities. The induction of cytotoxic cell death can be accompanied by membrane and DNA damage (39). In our study, MDA and 8-OHdG levels were increased in cells exposed to eugenol, eucalyptol, terpinen-4-ol, and camphor as a consequence of the membrane and DNA damaging effects of these test components on the cells, as showed in the results.…”
Section: Cytotoxic and Cytoprotective Effects Of Eugenol Eucalyptolsupporting
confidence: 81%
“…They induced membrane and DNA damage and cytotoxicity in H1299 cells at relatively higher concentrations than those that mediate their anticancer activities. The induction of cytotoxic cell death can be accompanied by membrane and DNA damage (39). In our study, MDA and 8-OHdG levels were increased in cells exposed to eugenol, eucalyptol, terpinen-4-ol, and camphor as a consequence of the membrane and DNA damaging effects of these test components on the cells, as showed in the results.…”
Section: Cytotoxic and Cytoprotective Effects Of Eugenol Eucalyptolsupporting
confidence: 81%
“…In the case of carvacrol, the most sensitive cell line was the lung adenocarcinoma A549 cell line (EC 50 =0.118±0.0012 mΜ), while Hep3B cells exhibited an intermediate effect (EC 50 =0.234±0.017 mΜ). In a study in 2003, carvacrol affected the viability of A549 cells in concentrations greater than 0.250 mΜ when treated for 24 h (27). The activity of carvacrol against A549 cells was also described in another study, where it was considered a weakly cytotoxic agent (EC 50 >0.1 mΜ), not only against these cells but also against the DLD-1 colon adenocarcinoma cell line (28).…”
Section: Discussionmentioning
confidence: 85%
“…In the recent past, its antitumor effect has arisen the concern of investigator. It was revealed that carvacrol has anti-proliferative properties on non-small cell lung cancer cells, A549, chronic myeloid leukemia cells, K562, Hep-2 cells, murine B16 melanoma cells and human metastatic breast cancer cells, MDA-MB231 (He et al 1997;Koparal and Zeytinoglu 2003;Lampronti et al 2006;Karkabounas et al 2006;Horvathova et al 2007;Arunasree 2010). Based upon the previous studies, it has been shown that carvacrol had a broad-spectrum of cytotoxic and anticancer activity.…”
Section: Introductionmentioning
confidence: 99%